2015
DOI: 10.1016/j.immuni.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The Autoimmunity-Associated Gene CLEC16A Modulates Thymic Epithelial Cell Autophagy and Alters T Cell Selection

Abstract: Summary CLEC16A variation has been associated with multiple immune-mediated diseases, including type 1 diabetes, multiple sclerosis, systemic lupus erythematosus, celiac disease, Crohn's disease, Addison's disease, primary biliary cirrhosis, rheumatoid arthritis, juvenile idiopathic arthritis and alopecia areata. Despite strong genetic evidence implicating CLEC16A in autoimmunity, this gene's broad association with disease remains unexplained. We generated Clec16a knock-down (KD) mice in the nonobese diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 44 publications
6
78
0
2
Order By: Relevance
“…Autophagy itself is also an important process in central selection as thymic epithelia utilize this process in effectively presenting to and negatively selecting T cells [48,49]. Thus it is possible that the aberrant autophagy in Copa syndrome itself may be promoting autoreactivity in the T cell compartment – perhaps directly explaining pathological autoantibody production.…”
Section: Pathogenesismentioning
confidence: 99%
“…Autophagy itself is also an important process in central selection as thymic epithelia utilize this process in effectively presenting to and negatively selecting T cells [48,49]. Thus it is possible that the aberrant autophagy in Copa syndrome itself may be promoting autoreactivity in the T cell compartment – perhaps directly explaining pathological autoantibody production.…”
Section: Pathogenesismentioning
confidence: 99%
“…Clec16a knockdown mice show reduced numbers of B cells,29 and are protected from autoimmunity 30. Further work is required to determine whether CLEC16A or DEXI is the relevant gene in this interval.…”
mentioning
confidence: 99%
“…One possible explanation for the discrepancy between results from Atg5 versus Atg7 deficient mice is that autophagy associated antigen presentation may utilize different components than the autophagy pathway itself (71, 7577). Interestingly, a recent report suggested that knockdown of Clec16a, an autophagy/mitophagy-associated protein (78, 79), is protective in the Non-obese diabetes (NOD) model of type 1 diabetes (80). They proposed that this was due to alterations in the generation and presentation of ligands by mTECs responsible for selecting diabetogenic T cells, rather than tolerance to islet associated antigens.…”
Section: Role Of Mtecs and Bm Apcs In Self-tolerancementioning
confidence: 99%